The Language of Deception : Weaponizing Next Generation AI - Hutchens, Justin; McClure,Stuart (2023)
A penetrating look at the dark side of emerging AI technologies In The Language of Deception: Weaponizing Next Generation AI, artificial intelligence and cybersecurity veteran Justin Hutchens delivers an incisive and penetrating look at how contemporary and future AI can and will be weaponized for malicious and adversarial purposes. In the book, you will explore multiple foundational concepts to include the history of social engineering and social robotics, the psychology of deception, considerations of machine sentience and consciousness, and the history of how technology has been weaponized in the past. From these foundations, the author examines topics related to the emerging risks of advanced AI technologies, to include: The use of Large Language Models (LLMs) for social manipulation, disinformation, psychological operations, deception and fraud The implementation of LLMs to construct fully autonomous social engineering systems for targeted attacks or for mass manipulation at scale The technical use of LLMs and the underlying transformer architecture for use in technical weapons systems to include advanced next-generation malware, physical robotics, and even autonomous munition systems Speculative future risks such as the alignment problem, disembodiment attacks, and flash wars. Perfect for tech enthusiasts, cybersecurity specialists, and AI and machine learning professionals, The Language of Deception is an insightful and timely take on an increasingly essential subject.
Keywords: Computer science; Artificial Intelligence